2014
DOI: 10.1200/jco.2014.32.15_suppl.e20631
|View full text |Cite
|
Sign up to set email alerts
|

Association of opioid requirement and cancer pain with survival in advanced non-small cell lung cancer.

Abstract: I would like to dedicate this thesis to my parents, Eugene and Joanne Zylla and Rich and Carol Bergenstal, who helped get me on the right path in both life and medicine; and my wife, Emily Zylla, who ensures I have the love and support I need every step along that path. And also to my research mentor and friend, Pankaj Gupta, who has given me the skills and confidence to forge my own road.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 37 publications
0
21
1
1
Order By: Relevance
“…Available data suggest that opioids influence vascular [ 6 ], pulmonary [ 7 , 8 ], and renal function [ 9 , 10 ] and cancer progression [ 6 ]. Our group (Gupta et al) found that higher opioid requirement was independently associated with shorter survival in patients with advanced prostate cancer [ 11 ] and lung cancer [ 12 ]. However, it remains to be determined whether high opioid use is a cause or consequence of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Available data suggest that opioids influence vascular [ 6 ], pulmonary [ 7 , 8 ], and renal function [ 9 , 10 ] and cancer progression [ 6 ]. Our group (Gupta et al) found that higher opioid requirement was independently associated with shorter survival in patients with advanced prostate cancer [ 11 ] and lung cancer [ 12 ]. However, it remains to be determined whether high opioid use is a cause or consequence of this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…Second, without complete original postoperative pain records, we cannot exactly exclude or evaluate the influence of pain factor. Zylla et al 44 reported pain was also a prognostic predictor of advanced NSCLC before chemotherapy. Third, the samples that use postoperative non-mu agonists seem a bit few.…”
Section: Discussionmentioning
confidence: 99%
“…Only few human studies have investigated either the impact of opioids per se or the relevance of expression of MORs in tumors on oncological outcomes (Table 1). In patients with NSCLC, 4 retrospective studies have indicated an association between the use of opioids and poor recurrence free-and/or overall survival [7,[64][65][66] . Three of these studies evaluated the use of opioid in the perioperative period and one was conducted in patients with advanced disease [7,[64][65][66] .…”
Section: Human Studiesmentioning
confidence: 99%
“…Opioids are also often used in oncological patients with moderate-to-severe pain secondary to metastatic disease or complications related to chemotherapy or radiation [3][4][5] . Over the last decade, several investigations have pointed towards a potential negative impact of opioids in patients undergoing cancer surgery and in those with advanced malignancies [6][7][8] . Specifically, it has been suggested that the use opioids could be responsible for short-and long-term postoperative adverse events including immunosuppression and cancer recurrence [6,9] .…”
Section: Introductionmentioning
confidence: 99%